2021
DOI: 10.3390/ijms22189687
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Mutations and Chromosomal Aberrations Induced by In Vitro and In Vivo Exposure to Furan

Abstract: Furan is a volatile compound that is formed in foods during thermal processing. It is classified as a possible human carcinogen by international authorities based on sufficient evidence of carcinogenicity from studies in experimental animals. Although a vast number of studies both in vitro and in vivo have been performed to investigate furan genotoxicity, the results are inconsistent, and its carcinogenic mode of action remains to be clarified. Here, we address the mutagenic and clastogenic activity of furan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The furan group exhibited redox imbalance with increased MDA and decreased both GSH and GPX-1. In alignment with our results, furan administration in animals has been associated with not only increased serum and tissue levels of MDA and a significant decrease of GSH and GPX-1 but also, was accompanied with a decrease in glutathione-S-transferase (GST), catalase (CAT) and superoxide dismutase (SOD) [15][16][17][18]. The decline in serum GSH "the body's master intracellular non-enzymatic antioxidant and the active coenzyme for the enzyme GPX-1" was probably due to its covalent bonding with cis-2butene-1,4-dialdehyde (BDA) which is the primary metabolite of furan formed under the metabolic influence of the liver enzyme cytochrome P450 2E1 (CYP2E1) [7].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The furan group exhibited redox imbalance with increased MDA and decreased both GSH and GPX-1. In alignment with our results, furan administration in animals has been associated with not only increased serum and tissue levels of MDA and a significant decrease of GSH and GPX-1 but also, was accompanied with a decrease in glutathione-S-transferase (GST), catalase (CAT) and superoxide dismutase (SOD) [15][16][17][18]. The decline in serum GSH "the body's master intracellular non-enzymatic antioxidant and the active coenzyme for the enzyme GPX-1" was probably due to its covalent bonding with cis-2butene-1,4-dialdehyde (BDA) which is the primary metabolite of furan formed under the metabolic influence of the liver enzyme cytochrome P450 2E1 (CYP2E1) [7].…”
Section: Discussionsupporting
confidence: 86%
“…There is much evidence for the involvement of the furan intermediate metabolite "BDA" that binds covalently to DNA leading ultimately to epigenetic changes and hyperplasia [9]. Also, BDA forms DNA single-strand breaks, DNAprotein cross-links and DNA adducts in mammalian cells that intermingled together yielding abnormal transcription and replication and may be mutations which are depicted as precancerous attributes [18,46,47]. Finally, in this study, Se advocated antiproliferative potential as was evident from the emerged results of Furan/Se group that exhibited a weak immunoexpression of PCNA and a significant decline in its mean area % in PCNA immuonstained sections of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in vivo DNA reactivity has not been rigorously excluded. In addition, there is evidence that oxidative stress and epigenetic alterations play a role [ 896 , 916 , 917 , 918 ].…”
Section: Epigenetic Carcinogens or Carcinogens With Uncertain Mode Of...mentioning
confidence: 99%
“…Thus, the authors proposed an indirect mechanism of genotoxicity, in which chronic toxicity followed by inflammation and secondary cell proliferation triggered the development of cancer following furan exposure. A recent report showed that furan caused chromosomal damage in both in vitro and in vivo models, and DNA inter‐strand cross‐links played an important role in furan clastogenicity (Russo et al., 2021).…”
Section: Toxicological Effects Of Furanmentioning
confidence: 99%